Big five personality and employees job commitment in the context of hotel industry: The moderating role of gender - Rusnah Ginsawat (2015)
The purpose of this study is to examine the relationship between big five personality dimension and employee job commitment in the context of hotel industry in Kata Kinabalu. In this study the variable of factor affecting employee job commitment are limited to extraversion, agreeableness, openness to experience, conscientiousness and neuroticism. The job commitment become one of the most important issue in people management especially when the organization deal with the new labor workforce that is Generation Y. Apart from that this study also aims to examine the moderating effect of demographic factor on employee job commitment. The scope of this study is focusing on the permanent hotel employees that working at five star hotel clusters in Kata Kinabalu. This study use convenient sampling as a sampling technique. To access the relationship between the exogenous variables and endogenous variable and dependent variable and the moderating effect, this study used Partial Least Square (PLS) technique that perform using Smart PLS version 2.0 program as a data analysis method. The result of the study indicates that only agreeableness, openness to experience, conscientiousness and neuroticism are positively and significantly correlated with the employee job commitment. Apart from that the result of the study proves that extroversion and demographic factors which is gender does not has a moderating effect on the relationship between big five personality dimension and job commitment.